Estuarine clay mineral distribution: Modern analogue for ancient sandstone reservoir quality prediction. Issue 6 (13th February 2019) - Griffiths, Joshua; Worden, Richard H.; Wooldridge, Luke J.; Utley, James E. P.; Duller, Robert A.; Edge, Rhiannon L.
Abstract: The spatial distribution of clay minerals in sandstones, which may both enhance or degrade reservoir quality, is poorly understood. To address this, clay mineral distribution patterns and host‐sediment properties (grain size, sorting, clay fraction abundance and bioturbation intensity) have, for the first time, been determined and mapped at an unprecedentedly high‐resolution in a modern estuarine setting (Ravenglass Estuary, UK). Results show that the estuary sediment is dominated by illite with subordinate chlorite and kaolinite, although the rivers supply sediment with less illite and significantly more chlorite than found in the estuary. Fluvial‐supplied sediment has been locally diluted by sediment derived from glaciogenic drift deposits on the margins of the estuary. Detailed clay mineral maps and statistical analyses reveal that the estuary has a heterogeneous distribution of illite, chlorite and kaolinite. Chlorite is relatively most abundant on the northern foreshore and backshore and is concentrated in coarse‐grained inner estuary dunes and tidal bars. Illite is relatively most abundant (as well as being most crystalline and most Fe–Mg‐rich) in fine‐grained inner estuary and central basin mud and mixed flats. Kaolinite has the highest abundance in fluvial sediment and is relatively homogenous in tidally‐influenced environments. Clay mineral distribution patterns in the Ravenglass Estuary have been strongly influenced by sediment supply (residence time) and subsequently modified by hydrodynamic processes. There is no relationship between macro‐faunal bioturbation intensity and the abundance of chlorite, illite or kaolinite. Based on this modern‐analogue study, outer estuarine sediments are likely to be heavily quartz cemented in deeply‐buried (burial temperatures exceeding 80 to 100°C) sandstone reservoirs due to a paucity of clay grade material (<0·5%) to form complete grain coats. In contrast, chlorite‐enriched tidal bars and dunes in the inner estuary, with their well‐developed detrital clay coats, are likely to have quartz cement inhibiting authigenic clay coats in deeply‐buried sandstones.